Analisis Mekanisme Pasar Dalam Islam, Sistem Ekonomi, dan Etika Pengawasan Pasar Serta Pasar Dalam Perspektif Sejarah Islam - Arifudin Arifudin; Avira Clairine Zahra; Dinda Ayu Oktaviona; Diyach Rachmawati; Marcella Pinasti (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This abstract discusses the role of market mechanisms in an Islamic perspective, as well as the implications and application of Islamic economic principles in the market system. Using the literature review method, this research collects, evaluates, and synthesizes relevant literature to gain an in-depth understanding of the topic. The results of the analysis show that markets in Islam are seen as a natural mechanism for exchanging goods and services, with prices determined by the forces of demand and supply. Islamic economic principles, such as justice, expediency, and the prohibition of usury, are the foundation for a fair and sustainable market system. Apart from that, the importance of market supervision and compliance with market ethics is also emphasized to maintain balance and fairness in economic activities. The analysis also highlights prohibitions in Islamic transactions that can cause market distortions. In addition, this abstract presents a comparison between conventional economic systems (capitalist, socialist, and mixed) with Islamic economic systems, which are based on sharia principles. Thus, this research contributes to understanding the concept of market mechanisms in Islam and formulating economic policy recommendations that are in accordance with Islamic values.